Adapting Screening, Brief Intervention, and Referral to Treatment for Alcohol and Drugs to Culturally Diverse Clinical Populations. Issue 5 (September 2015) - Manuel, Jennifer K.; Satre, Derek D.; Tsoh, Janice; Moreno-John, Gina; Ramos, Jacqueline S.; McCance-Katz, Elinore F.; Satterfield, Jason M.
Abstract : Objectives: To review the literature on the screening, brief intervention, and referral to treatment (SBIRT) approach to alcohol and drug use with racial and ethnic subgroups in the United States and to develop recommendations for culturally competent SBIRT practice. Methods: Articles reporting on the use of SBIRT components (screening, brief intervention, referral to treatment) for alcohol and drug use were identified through a comprehensive literature search of PubMed from 1995 to 2015. Results: A synthesis of the published literature on racial and ethnic considerations regarding SBIRT components (including motivational interviewing techniques) was created using evidence-based findings. Recommendations on culturally competent use of SBIRT with specific ethnic groups are also described. Conclusions: On the basis of the literature reviewed, SBIRT offers a useful set of tools to help reduce risky or problematic substance use. Special attention to validated screeners, appropriate use of language/literacy, trust building, and incorporation of patient and community health care preferences may enhance SBIRT acceptability and effectiveness. Practice Implications: Providers should consider the implications of previous research when adapting SBIRT for diverse populations, and use validated screening and brief intervention methods. The accompanying case illustration provides additional information relevant to clinical practice.